Density, connectedness and attentional capture in hierarchical patterns: evidence from simultanagnosia. - Montoro, P; Luna, D; Humphreys, G (2011)
We examined the effects of different grouping cues (item density, number and connectedness) on the ability of a patient with simultanagnosia (GK) to identify compound stimuli. In Experiment 1, the effects of density and connectedness on the recognition of global and local forms were examined. In Experiment 2, the spatial distance of local elements was manipulated by varying the size of the global forms and the number of local elements, to assess whether the distance between the local elements or their number determined the effects on global/local processing in disconnected patterns. The results showed that high item density and connectedness, each facilitates the grouping of local elements into global shapes, determined the explicit recognition of global stimuli in simultanagnosia. Moreover, in addition to any bias to attend to the local level, there was also evidence for attentional capture by stimuli at the global level. The data indicate that grouping processes still operate in simultanagnosia and can overcome biases to select at a local level. Any biases in selection can also be compounded by poor attentional disengagement.